Phytochemical Profile and Antimicrobial Activity of Citrus Medica (Limau Susu) Fruit Peels Extract - Anak Simona, Sophia; Zamakshsharia, Nor Hisam (International Journal of Biotechnology and Biomedicine (IJBB), 2024)
Citrus medica, also known as “Limau Susu” in Malaysia, is generally called a citron in English. Citrus medica is one of the four original citruses, and many of today's citrus varieties are descended from this variety. Six Citrus medica peel extracts were produced from this research using the maceration technique and percentage yield were calculated. Each different extraction procedure inevitably results in variances in biological activity. This study aimed to assess extraction procedures' impact on the yield and microbial activity of Citrus medica using the disc-diffusion method. In addition, GC-MS was carried out to identify additional components (qualitative). The phytochemical analysis of each extract was done to distinguish the chemical constituent between the extracts. Results show that both dry and fresh samples of the Citrus medica plant give percentage yield of methanol extract. Meanwhile, the hexane extract shows the highest anti-microbial activities due to the presence of 3 major compounds. The high antimicrobial activity is due to the presence of Oxacycloheptadec-8-en-2-one, 2-Cyclohexen-1-ol, and Terpineol as major compounds in the extract.